Development of a buffalo herd health and breeding protocol in Sabah - Saad, Mohd Zamri; Kasim, Azhar; Abu Bakar @ Zakaria, Md Zuki; Othman, Rafidah (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2013)
This project aimed at improving the herd health and breeding protocol for buffalo in Sabah by implementing protocols on buffaloes in Sabah and transfering related knowledge to the industry via farm manager and staffs. Prior to implementing the improved protocol, buffalo performance in the last 8 years were analysed Following implementation of protocols, there were significant improvements, particularly in the quality of grass from 8% protein to 11% protein, reduced rate of mortality from 11.3% to 5.2% and improved rate of pregnancy from 41% to 67.5%. These increased the farm income from RM74,857.00 to RM149,330.00.